2022
DOI: 10.3389/fpls.2022.927200
|View full text |Cite
|
Sign up to set email alerts
|

A Functional Genomics View of Gibberellin Metabolism in the Cnidarian Symbiont Breviolum minutum

Abstract: Dinoflagellate inhabitants of the reef-building corals exchange nutrients and signals with host cells, which often benefit the growth of both partners. Phytohormones serve as central hubs for signal integration between symbiotic microbes and their hosts, allowing appropriate modulation of plant growth and defense in response to various stresses. However, the presence and function of phytohormones in photosynthetic dinoflagellates and their function in the holobionts remain elusive. We hypothesized that endosym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Changes in the numbers of the OJIP transients further substantiate the synergistic impact of co-stress on photochemical electron transport, consequently exerting stronger effects on the photosynthesis of Symbiodiniaceae (Figures g and h). A recent study demonstrated that phytohormones play vital roles in signal transduction pathways in the response of the bleaching-inducible environmental stresses . The change in the relative abundance of salicylic acid (SA) may imply that the level of metabolic response to environmental stress of Symbiodiniaceae had increased under co-stress conditions (Figure c).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Changes in the numbers of the OJIP transients further substantiate the synergistic impact of co-stress on photochemical electron transport, consequently exerting stronger effects on the photosynthesis of Symbiodiniaceae (Figures g and h). A recent study demonstrated that phytohormones play vital roles in signal transduction pathways in the response of the bleaching-inducible environmental stresses . The change in the relative abundance of salicylic acid (SA) may imply that the level of metabolic response to environmental stress of Symbiodiniaceae had increased under co-stress conditions (Figure c).…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that phytohormones play vital roles in signal transduction pathways in the response of the bleaching-inducible environmental stresses. 48 The change in the relative abundance of salicylic acid (SA) may imply that the level of metabolic response to environmental stress of Symbiodiniaceae had increased under co-stress conditions (Figure 3c). Accordingly, the co-stress elicited a notable increase in chlorophyll c content and chlorophyll metabolite levels on the fourth day, potentially serving as a compensatory mechanism within the coral that enhances photosynthetic efficiency (Figure S8).…”
Section: Presence Of Herbicide Prometryn Alteringmentioning
confidence: 99%